Śląski nacjonalizm? : myśl polityczna Ruchu Autonomii Śląska - Slenzok, Norbert (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2019)
The presented paper is aimed at description and classification of Silesian Autonomy Movement’s (R AŚ) controversial activity in regard of its political thought and the role played by nationalism thereof. More precisely, author of the article focuses on the question whether the ideas promoted by R AŚ can by viewed as nationalist. As a result of the scrutiny, they turn out to be nationalist only in the broadest meaning of this term, in the light of which nationalism refers to all movements seeking autonomy, unity and identity of the respective nations. In author’s judgement it is above all due to peculiar, pluralistic and inclusive concept of Silesian nationality, emphasising the diversity and complexity of Silesian identities. On the other hand, the author discusses the obstacles brought about by such an idea, that may ultimately imperil the process of creating Silesian nation, as well as considerable discrepancy between abovemantioned concept and anti-Polish rhetoric, presented from time to time by R AS and its leader Jerzy Gorzelik
Keywords: Ruch Autonomii Śląska (RAŚ); Górny Śląsk; narodowość śląska; nacjonalizm; myśl polityczna